Three new species and growth patterns in Hechtia (Bromeliaceae: Hechtioideae) - Ramírez, Ivón; Jiménez, Carlos F.; Carnevali, Germán; Pinzón, Juan Pablo (Phytotaxa, 2014)
Three new species of Hechtia from the Mexican State of Oaxaca are herein proposed as new: Hechtia flexilifolia, H. huamelulaensis, and H. nivea, from the physiogeographical provinces of Mixteca Alta, Costas del Sur, and Sierras Centrales de Oaxaca respectively. All three species are described and illustrated. Iconography provided features plants in habitat and under cultivation. An assessment of their conservation status sensu IUCN criteria is presented as well. We also discuss and illustrate the three growth patterns identified at this time in the genus.